Association of the sagittal cervico-thoracic clinical posture with radiological thoracic inlet alignment in chronic neck pain subjects. - Rani, Babina; Paul, Abhijit; Negi, Sandeep; Causevic, Denis; Dhillon, Mandeep S. (Journal of Bodywork & Movement Therapies, 2025)
The presence of altered sagittal cervical balance and faulty posture has been observed in individuals with neck pain. However, there is a lack of literature investigating the relationship between radiological thoracic inlet alignment and clinical sagittal cervico-thoracic posture. This cross-sectional study aims to investigate these clinico-radiological associations, analyze their correlation with pain variables, and explore the diagnostic significance of thoracic inlet parameters for chronic neck pain (CNP). 88 subjects (N = 44 each in CNP and Control group) were recruited. T1 Slope (T1S), Thoracic inlet angle (TIA), Neck tilt (NT) were assessed on lateral cervical radiograph, and Craniovertebral angle (CVA), High thoracic angle (HTA), Sagittal head angle (SHA) were photographically analysed. Pain was quantified in terms of intensity and functional disability. Craniocervical flexion test (CCFT) assessed the deep neck flexors (DNF) performance. After normality check, between-group comparisons utilized Unpaired t -test or Mann-Whitney U test. CNP group had lower T1S, and higher TIA, NT. The TIA had significant correlation with CVA and HTA (r s = −0.32, −0.30 respectively) in asymptomatic group, but not in CNP subjects. Patients with severe pain/disability had weaker DNF. Symptomatic group showed age-related declines in SHA, CVA and CCFT. Logistic regression revealed T1S (<26.36°) and NT (>47.41°) had diagnostic significance for CNP. Neck pain corresponded with distinct postural, radiological, and clinical alterations compared to controls. Thoracic inlet parameters (primarily TIA) influenced cervicothoracic posture in asymptomatic individuals, but pain disrupted these associations, highlighting the complex interplay between alignment, posture, and symptomatology. • Chronic neck pain is linked with altered cervico-thoracic posture and thoracic inlet alignment. • Thoracic inlet parameters (mainly TIA) influenced posture in controls, but pain disrupted these links in neck pain subjects. • Deep neck flexor weakness correlated with higher pain intensity and functional disability. • Symptomatic group showed age-related declines in SHA, CVA, and CCFT performance.